First aid a guide for physical & health educators / Muhamad Nur Fariduddin Abdul Aziz - Abdul Aziz, Muhamad Nur Fariduddin (UiTM Press, 2024)
This guidebook embarks on a journey to understand the fundamental of first aid the underlying principles for each disease, disorder, condition and effective management.Understanding first aid can be challenging.